Kajian Laik Fisik Sanitasi Dan Kualitas Mikrobiologis Depot Air Minum (DAM) Dibawah Program Pembinaan Dan Pengawasan Dinas Kesehatan Kabupaten Hulu Sungai Utara - Rosmiaty Rosmiaty; Andy Mizwar; Rizmi Yunita; Erma Agusliani (EnviroScienteae, 2019)
Determining category of physical appropriateness of DWS under health office development and controlling program of Hulu Sungai Utara Regency, Determining Microbiology quality of  DWA under health office development and controlling program of Hulu Sungai Utara Regency, analyzing the correlation of physical appropriateness and microbiology quality if DWS under health office development and controlling program of Hulu Sungai Utara Regency. This is a quantitative study using cross-sectional research design in which the research was conducted in a certain period of time, the location of research was in 10 service area of the public health center in 9 subdistricts under health office development and controlling program of Hulu Sungai Utara Regency. It was found that 30 DWS (Drinking Water Storehouse) is under health office development and controlling program of Hulu Sungai Utara Regency, DWS which categorized as physically not Appropriate (TLF) was 20 DWS (66,7%) and categorized as physically appropriate (LF) was 10 DWS (33,3%). Microbiology quality of Balangan, Tabalong, Negara, Tangkawang and Rantau Bujur Darat River were excess the standard of quality of class I intended for the drinking water source. Microbiology quality of water source (PDAM) from 30 samples, it was found that 14 samples (46,7%) contained Coliform and E. coli, there were 2 samples (6,7%) contained only Coliform. Quality of microbiology and water product of  30 DWS, it was found that 2 DWS contained Coliform, all water of DWS production did not contain  E.coli. Statistical test of the correlation of physical appropriateness and microbiology quality of river water cannot be conducted because all samples have the same category which is TMS so that there was no difference in result data of category determination. There was no significant difference between physical appropriateness with microbiology quality of Coliform (p=0,260) and E.coli (p = 0,235) raw water of DWS. There was no significant correlation of physical appropriateness with microbiology quality of Coliform (p = 0,540) water product of DWS, meanwhile for statistical test for correlation of physical appropriateness and microbiology quality of E.coli of water product cannot be conducted because there was no difference in result data of category determination so that all samples has the same category.